Hukum dan Etika Profesi Hakim dan Pegawai Pengadilan di Indonesia - Kaharu, Natan; Moonti, Roy Marthen; Ahmad, Ibrahim; Kasim, Muslim A. (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the enforcement of law and ethics in the profession of judges and court employees in Indonesia. Ethics and integrity are crucial elements in maintaining credibility and fairness in the justice system. Although there are strict regulations and codes of ethics, ethical violations and corruption cases still often occur, indicating the need for stricter supervision and sanctions. This study also highlights the importance of continuous ethics education and improving the welfare of judges and court employees as an effort to reduce unethical behavior. In addition, the application of information technology to improve transparency and accountability in the judicial process is also considered an effective solution. In conclusion, consistent enforcement of law and ethics and a strong commitment from all parties involved are essential to creating a fair and transparent justice system in Indonesia.